2005
DOI: 10.1017/s1355617705050666
|View full text |Cite
|
Sign up to set email alerts
|

Visuomotor control in survivors of childhood acute lymphoblastic leukemia treated with chemotherapy only

Abstract: Treatment for childhood acute lymphoblastic leukemia (ALL), which includes CNS prophylaxis, is associated with central and peripheral neurotoxicity. The purpose of the present study was to analyze the effects of chemotherapy on various levels of visuomotor control in survivors of childhood ALL treated without cranial irradiation, and to identify risk factors for possible deficits. Visuomotor function was compared between children after treatment for ALL (n 5 34), children after treatment for Wilms tumor, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 76 publications
4
58
0
2
Order By: Relevance
“…However, we did observe lower scores, mainly in the number of correct responses on part 3 of the test that investigated selectivity/alternation, compared with the scores of healthy children in the same age group. These findings are consistent with the observations by Buizer et al (2005) who reported that children with ALL and who received standard treatment had similar performance as healthy children in attention and information processing, with the exception of attention flexibility. Mennes et al (2005) reported that their results, which were similar to the present results, disagreed with some findings obtained in children who were cured of ALL and experienced attention capacity problems.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, we did observe lower scores, mainly in the number of correct responses on part 3 of the test that investigated selectivity/alternation, compared with the scores of healthy children in the same age group. These findings are consistent with the observations by Buizer et al (2005) who reported that children with ALL and who received standard treatment had similar performance as healthy children in attention and information processing, with the exception of attention flexibility. Mennes et al (2005) reported that their results, which were similar to the present results, disagreed with some findings obtained in children who were cured of ALL and experienced attention capacity problems.…”
Section: Discussionsupporting
confidence: 92%
“…According to Mulhern & Palmer (2003) and Buizer et al (2005), several of the core deficits exhibited by ALL survivors are defined by the term "executive function," characterized by the capacity to allocate attention resources and organize behavior and thinking, which rely on the integrity of the prefrontal cortex. We found that the lowest scores were in the group of children in treatment compared with the children off treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No differences were detected on any neurocognitive measure between patients treated on different doses of MTX. This study was discussed in the context of the reports by Buizer et al [98,99] who identified subtle deficits in attention and visuomotor control in ALL survivors who received higher doses of IV-MTX. ALL survivors also have more behavioral and educational problems [100].…”
Section: Neurocognitive Impact Of Antileukemia Therapymentioning
confidence: 89%
“…However, a cancer diagnosis disrupts opportunities for normal development and PA participation because of hospitalization and treatment side effects, both of which contribute to physical impairments and reduced motivation. 12 Specific to ALL survivors, evidence has suggested that vincristine 13,14 and methotrexate 15 treatments directly relate to motor performance impairments during and after treatment. Anthracycline treatment has well-documented, potentially long-term cardiotoxic side effects, and it potentially limits physical function.…”
mentioning
confidence: 99%